2020
DOI: 10.1002/stco.202000011
|View full text |Cite
|
Sign up to set email alerts
|

Joints with lockbolts in steel structures – Part 1: Lockbolt technology

Abstract: Many mechanical joints in steel structures use conventional bolts. Nevertheless, this proven jointing technology has some significant disadvantages. These basically include the high levels of scatter during application of the assembly preload using the torque-controlled tightening process, the risk of loosening during cyclic loads due to transverse displacement of the components and the low fatigue resistance under axial loading. Lockbolt technology was invented as long ago as the 1930s and mainly used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To date, no consensus has been reached regarding the design criterion of HSLFG joints, which hinders the application of HSLFG joints in steel bridges (Glienke et al, 2020a(Glienke et al, , 2020b. In general, the lockbolted joint can be designed as either slip-resistant or bearing-type, depending on different load-bearing patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no consensus has been reached regarding the design criterion of HSLFG joints, which hinders the application of HSLFG joints in steel bridges (Glienke et al, 2020a(Glienke et al, , 2020b. In general, the lockbolted joint can be designed as either slip-resistant or bearing-type, depending on different load-bearing patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the pretension of lockbolt provided very limited friction force between aluminum alloy plates. Although the lockbolted connections, normally used for aluminum alloy plates, can be designed as bearing-type, some applications call for lockbolt use in slip-resistant connections, such as lattice towers for wind turbines in Germany (Glienke et al, 2020a(Glienke et al, , 2020b. Ebert et al (2017) experimentally compared the slip-resistant connections of both the high-strength bolts and bobtail lockbolts, which indicated that the tightening procedure for lockbolts is different from the high-strength bolts which adopt torque method.…”
Section: Introductionmentioning
confidence: 99%
“…Lockbolt technology -also known as the Huckbolt ® after its inventor -represents an alternative to conventional bolted joints [6]. Lockbolts have a number of advantages, which are outlined in this article.…”
Section: Introductionmentioning
confidence: 99%